The Role of Digitization in Promoting the Globalization of the Halal Industry "Halal Chain Platform as a Model" - Heyam Sami Al-Zaghbi (Ta'amul: Journal of Islamic Economics, 2023)
The Arab Organization for Industrial Development and Mining affiliated to the League of Arab States launched the International Forum for Halal Accreditation Bodies, as an Arab innovative initiative in the Halal industry inspired by the UAE Halal initiative, which in turn leads international efforts towards the globalization of the Halal industry aimed at strengthening Dubai's position as the global capital of the Islamic economy. In line with the technological development and digital transformation that the world is witnessing today, and in line with the Emirati initiative to globalize the Halal industry, HLC Technologies has launched the HalalChain platform, which specializes in tracking the Halal industry, based on Blockchain technology, at the company's headquarters in Dubai. It is a smart, decentralized platform, based on "Blockchain" technology and "Internet of Things", to enable entities, institutions and companies to track all stages of food production, processing and distribution, and to track the production of pharmaceuticals and cosmetics across all elements of the supply chain, to ensure safety and compliance. All health standards and controls. The study aims to demonstrate the role of digitization in improving productivity and promoting economic growth, and its role in spreading the globalization of the Halal industry. The study also highlights the importance of the Halal Chain platform in facilitating the process of trade exchange and strengthening the role of the state in the field of industry and trade, The study concluded that the Halal Chain platform is not only a platform for tracking products, but rather a comprehensive Islamic system on the Block Chain.